New venture management : the entrepreneur's roadmap for development, management, and growth - Kuratko, Donald F.; Hornsby, Jeffrey S. (Jeffrey Scott), 1959- (New York : Routledge, 2021)
"The third edition of this practical textbook provides an introduction to the world of new and emerging ventures and to the fundamentals of effective new venture management, including such diverse activities as planning, marketing, financing, and growth. This textbook is divided into four distinct parts, guiding readers through the entire new venture management process and focusing in turn on ideas and opportunities, planning, finance, and management challenges. All chapters of this revised edition feature international cases, and the complete business plan has been replaced with a contemporary version. Other new elements to the third edition include: Expanded coverage of the Lean Startup methodology Improved focus on the development and importance of teams A new section on the emergence of equity crowdfunding Further discussion of ethics and the dangers of dramatic scaling Presented in an easy-to-understand style, this book will be a valuable resource for undergraduate and postgraduate students in entrepreneurship and new venture management classes, as well as active new venture owners and managers. Online resources include an instructor's manual, test bank, PowerPoint slides, and additional materials to aid instructors and students in applying their knowledge"--
OCLC-licensed vendor bibliographic record.
Keywords: New business enterprises; Venture capital; Entrepreneurship; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / New Business Enterprises